Analisis tingkat pemahaman mahasiswa teknologi rekayasa informatika industri terhadap penggunaan bahasa pemrograman python dalam pembelajaran Pemrograman - Ali Musthofa Baharudin; Aqsha Maulana Ilham; Arum Sita Resmi; Bella Firdha Azkia; Naufal Reswara; Ihsan Tanama Sitio (Fakultas Teknologi Informasi, Universitas Kristen Satya Wacana, 2026)
Python programming has become a fundamental competence in the digital era, yet students often struggle to transform algorithmic logic into functional code. This gap between conceptual understanding and practical implementation skills requires a thorough investigation into learning challenges within the Industrial Informatics Engineering Technology (TRIN) program at Politeknik Manufaktur Bandung. Grounded in Bloom's Revised Taxonomy and Cognitive Load Theory, this descriptive quantitative study utilized a Likert-scale questionnaire and an objective comprehension test administered to 87 third-year students. Data were analyzed using descriptive statistics to map performance across three aspects: conceptual understanding, syntactic comprehension, and implementation ability. Results indicate the conceptual aspect achieved the highest average of 4.15, followed by syntax at 3.56 and implementation at 3.54, with objective test accuracy rates of 76.09%, 65.52%, and 67.36%, respectively. Major obstacles identified include difficulties with looping, debugging, and comparison operators. Therefore, enhanced structured practice and Project-Based Learning approaches are recommended to strengthen students' implementation competencies.